Moving walkways as a way to navigate in virtual reality - Mäkipelto, Matias (My University, 2023)
In this thesis, we will look at moving walkways as a locomotion technique in VR. We will take a look at how much they induce motion sickness, what speed should virtual moving walkways have, and should their shape differ from a physical moving walkway. To achieve this, a virtual environment was created where users can test moving walkways of different shapes and compare them to controller movement. We find that moving walkways can potentially be used to reduce VR sickness experienced. The speed of moving walkways should be adjustable to suit people with different tolerances for VR sickness. One has a lot of freedom with the shape of a moving walkway, but it should include a static frame of reference and it should fit the aesthetics of the environment.
Keywords: VR, virtual reality, VR sickness, moving walkway, locomotion technique